Measuring hospital-wide activity volume for patient safety and infection control: a multi-centre study in Japan - Fukuda Haruhisa; Imanaka Yuichi; Hayashida Kenshi (BMC, 2007)
Abstract Background In Japan, as in many other countries, several quality and safety assurance measures have been implemented since the 1990's. This has occurred in spite of cost containment efforts. Although government and hospital decision-makers demand comprehensive analysis of these activities at the hospital-wide level, there have been few studies that actually quantify them. Therefore, the aims of this study were to measure hospital-wide activities for patient safety and infection control through a systematic framework, and to identify the incremental volume of these activities implemented over the last five years. Methods Using the conceptual framework of incremental activity corresponding to incremental cost, we defined the scope of patient safety and infection control activities. We then drafted a questionnaire to analyze these realms. After implementing the questionnaire, we conducted several in-person interviews with managers and other staff in charge of patient safety and infection control in seven acute care teaching hospitals in Japan. Results At most hospitals, nurses and clerical employees acted as the main figures in patient safety practices. The annual amount of activity ranged from 14,557 to 72,996 person-hours (per 100 beds: 6,240; per 100 staff: 3,323) across participant hospitals. Pharmacists performed more incremental activities than their proportional share. With respect to infection control activities, the annual volume ranged from 3,015 to 12,196 person-hours (per 100 beds: 1,141; per 100 staff: 613). For infection control, medical doctors and nurses tended to perform somewhat more of the duties relative to their share. Conclusion We developed a systematic framework to quantify hospital-wide activities for patient safety and infection control. We also assessed the incremental volume of these activities in Japanese hospitals under the reimbursement containment policy. Government and hospital decision makers can benefit from this type of analytic framework and its empirical findings.